ANALISIS PENDAPATAN DAN EFISIENSI USAHATANI JAGUNG PADA LAHAN KERING DI KECAMATAN WAWO KABUPATEN BIMA - Ni Made Nike Zeamita Widiyanti; Ni Made Wirastika Sari; Soekartini Soekartini (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2023)
Increasing maize production can be done by utilizing dry land as a potential land for maize farming development. This research aims to determine the income of corn farming and calculate the efficiency of corn farming on dry land in Wawo District, Bima Regency. Based on the research results, the value of corn farming income amounted to Rp 4,886,423.69/ha. The efficient value of farming based on the calculation of the R/C ratio is 1.37, meaning that corn farming is in the efficient category to be implemented. Keywords: Maize, Farm Income, Farm Efficiency